INHIBITORY EFFECTS OF PLANT COMPOUNDS ON ENZYMATIC AND ACTIVITIES INDUCED BY A SNAKE PHOSPHOLIPASE A2 - PEREAÑEZ, Jaime A.; NÚÑEZ, Vitelbina; PATIÑO, Arley C.; LONDOÑO, Mónica; QUINTANA, Juan C. (Vitae, 2011)
Polyphenolic compounds have shown to inhibit toxic effects induced by snake venom proteins. In this work, we demonstrate that gallic acid, ferulic acid, caffeic acid, propylgallate and epigallocatechingallate inhibit the enzymatic activity of a phospholipase A2 (PLA2), using egg yolk as substrate. The IC50 values are between 0.38 – 3.93 mM. These polyphenolic compounds also inhibit the PLA2 enzymatic activity when synthetic substrate is used. Furthermore, these compounds decreased the cyotoxic effect induced by a myotoxic PLA2; specifically, epigallocatechin gallate exhibited the best inhibitory capacity with 90.92 ± 0.82%, while ferulic acid showed the lowest inhibitory activity with 30.96 ± 1.42%. Molecular docking studies were performed in order to determine the possible modes of action of phenolic compounds. All polyphenols showed hydrogen bonds with an active site of enzyme; moreover, epigallocatechingallate presented the strongest binding compared with the other compounds. Additionally, a preliminary structure-activity relationship analysis showed a correlation between the IC50 and the topological polar surface area of each compound (p = 0.0491, r = -0.8079 (-0.9878 to -0.2593)), which indicates the surface area required for each molecule to bind with the majority of the enzyme. Furthermore, our results show that propylgallate and epigallocatechingallate are two novel natural products with anti-myotoxic potential. The topical application of these plant polyphenols at the bite site could lead to prevent myotoxicity; however, further in vivo studies would be necessary to confirm the in vitro results.